Sequence Analysis of HN and F Genes of a less Virulent Newcastle Disease Virus Isolated from Unvaccinated Village Chicken - Ponnusamy, P.; Kirubaharan, J. John; Chandramohan, Andrew (International Journal of Poultry Science, 2009)
The HN and F genes of the D58 isolate have coding senquence of 577 and 553 amino acids respectively. The HN gene has stalk (1-143) and globular head (123-571) regions with transmembrane domain at positions 25-45, sialic acid residue at 234-239, glycosylation sites at 119, 341, 433, 481 and 538 and cysteine residues at 172, 186, 196, 238, 247, 251, 344, 455, 461, 465, 531 and 542. The glycosylation site at 508 specific for virulent strains and cysteine residue at 123 were absent in D58 isolate. The F gene has transmembrane domains at positions 15-25 and 501-523 and glycosylation sites at 85, 191, 366, 447, 471 and 541. The fusion protein cleavage site has amino acids GRQGRL and fusion peptide starts with leucine. The HN and F genes have 26 and 23 B cell epitopes respectively. The D58 isolate was grouped with less virulent strains in phylogenetic analysis.